Introduction to special issue on digitalization, labour and global production - Gale Raj-Reichert; Sabrina Zajak; Nicole Helmerich (Competition & Change, 2021)
This special issue contributes to the emerging literature on digitalization and its impact on work and workers in global systems of production. Three key themes are featured in the collection of papers. They are on the relationship between the use of digital communication technologies and power relationships, working conditions of online workers or crowd-workers, and shifting geographies of production. The papers also largely focus on the global South, contributing to research on digitalization and labour which has thus far tended to examine large and higher income countries mainly in the global North. This introductory article expands on and situates the papers broadly within the literature on digitalization and labour and within the three themes more specifically, and discusses their implications for future research.
Keywords: 330; digitalization; labour; workers; global value chains; power; crowdwork; production